ADVANTAGES AND CLINICAL LIMITATIONS OF STAINLESS-STEEL CROWNS IN PEDIATRIC DENTISTRY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Stainless steel crowns (SSCs) have become a cornerstone in pediatric dentistry due to their durability, cost-effectiveness, and ease of placement. These crowns provide full coronal coverage for primary and young permanent teeth, especially in cases of extensive caries or developmental defects. Despite their numerous advantages, SSCs are not without limitations, including aesthetic concerns and potential challenges in clinical application. This article explores the advantages and clinical limitations of SSCs, providing a comprehensive analysis supported by recent literature and clinical studies.